Optimization in Sign System Design UPN “Veteran” of East Java - Aryo Bayu Wibisono; Iwan Wahyudianjo (Future Science)
UPN “Veteran” of East Java, Surabaya, East Java, Indonesia is a state university with State Defense characteristic which have its own vision, mission and reputation both on the national and international level. The reputation proven by the A rank in university accreditation scale (AIPT A). At this phase, infrastructure had become essential factor and therefore also become an important background of physical image. One of the physical image development effort is by optimizing the sign system on the campus building. On such basis, this study aims to fix the infrastructure through an integrated sign system. The sign system meticulously designed based on research to communicate the values of State Defense as well as the characteristics of UPN “Veteran” of East Java. The data collection in this research uses quantitative research methodology and supported by qualitative method. This research is conducted at UPN “Veteran” of East Java involving active campus residents. The research is also supported by design-related journals and books.